Continuance Intention of Users to Use E-Learning in Professional Qualification Certification: A PRISMA-based Systematic Literature Review. - Huiying, Long; Bidin, Rosmiza Binti Haji; Mustakim, Siti Salina Binti; Sharipudin, Mohamad-Noor Salehhuddin; Li, Niu; Haoran, Liu (Pertanika Journal of Social Sciences & Humanities, 2026)
This paper aims to identify and analyse the key factors that affect the continuance intention of users to use e-learning for professional qualification certification and conduct a comprehensive review of the main research results in the literature. While systematic reviews on e-learning continuance intention exist, few specifically focus on the unique context of professional certification, which is characterised by exam-driven pressures and career-oriented motivations. This study addresses this gap. The study adopts the systematic literature review (SLR) method, draws on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, and retrieves relevant articles from electronic databases such as Web of Science, Scopus, Emerald, and Science Direct. The research focuses on key factors and user characteristics. The results of the systematic analysis show that the main factors affecting the continuance intention of users include: (1) the technical quality and functionality of the learning platform, system usability, platform functions and technical support; (2) users' internal learning motivation and demand for professional certification; (3) the quality of course design, customisation flexibility and learning efficiency; (4) social influence, the construction of learning community and environment factors have a significant effect on user emotions and resource security. The study provides detailed, context-specific optimisation suggestions for e-learning system designers and educational institutions. Improving technical performance, enhancing course design, and strengthening social support can significantly improve users continued use intention, especially in the rapidly changing environment after the epidemic.